Efektivitas Pembelajaran Daring Pada Mata Pelajaran Matematika Di Kelas VIII SMP Negeri 7 Kupang Pada Masa Pandemi Covid-19 - Boleng, Yasinta Christanti (Universitas Nusa Cendana, 2024)
The Corona virus disease 2019 pandemic caused the government issued a policy that changed the habits of schooling in Indonesia which previously adopted face to face system into online learning. This suddenly in the learning process certainly affects the effectiveness of learning and on the process of running this online learning system there are obstacles experienced. The purpose of this study was to describe the effectiveness of online learning and to find out the obstacles in online learning in mathematics subject in VIII Class of SMP Negeri 7 Kupang during the covid 19 pandemic. This study uses a survey method with data collection techniques using a questionnaire in the google form. From the result of this research, online learning of mathematics subject in VIII Class of SMP Negeri 7 Kupang during the covid 19 pandemic was effective and the value of the effectiveness of online learning in mathematics subject was greater than 65. This can be seen from the result of the t test which shows that t count is 16.295 > t table is 1.6909, then Ho accepted and Ha rejected. From the result of the research and discussion it can be seen that the aspects that most support this effectiveness are aspect of motivation and interest. The obstacle that is most often experienced is the internet network which is difficult or sometimes interrupted.